MARIA TELADAN DALAM BERIMAN DI TENGAH PANDEMI COVID-19 - Adon, Mathias Jebaru; Depa, Siklus Rikardus (Sekolah Tinggi Teologi Hagiasmos Mission, 2022)
The research aims to confirm faith for everyone to survive the storm of the Covid-19 Pandemic and not lose their faith. Therefore, it takes a figure who can be an example of how to deal with suffering. One of the figures who can be an example is Mary the mother of Jesus. Maria in her life has shown how suffering does not prevent her from surrendering herself more to God. Mary shows how to behave as a believer by making suffering as an opportunity to surrender more and more to God's will. Through total submission to God Mary grew in a firm faith in God so that suffering did not prevent her from seeing God's plans and works behind the suffering she received. This research uses library and interview methods. Interviews were conducted by telephone or video call. This study finds that by reflecting on Mary's faith, the faithful are not trapped in the reality of suffering but find God's grace behind suffering so that humans do not despair and lose their faith. Therefore, Christians are invited to reflect on Mary's faith.